IMPLEMENTASI MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PADA SISWA KELAS IX.9 SMP NEGERI 10 KOTA BEKASI - ., Rapisah; Supriadi, Jabar (Turats, 2016)
The purpose of this study is to improve learning outcomes Islamic religious education through learning model make a match in the class IX.9 SMP Negeri 10 Bekasi. The subjects were students of class IX.9 SMP Negeri 10 Bekasi as 38 students. The method used in the class action research consisted of two cycles. The technique of collecting data through observation, tests, interview, and discussions. Results of the study data showed that an increase in student learning outcomes between before being given treatment with after treatment is given through the model make a match. The test results obtained pre-cycle average value of 69,00 with learning completeness 0%. After given treatment with learning model make a match the test results obtained cycle I average value of 82,55 with learning completeness 92,11% and cycle II average value of 91,45 with learning completeness 100%. It is concluded that learning through models make a match can improve learning outcomes Islamic religious education in the class IX.9 SMP Negeri 10 Bekasi